Introduction to special issue: Arctic marine resource governance. (October 2016) - Fernandez, Linda; Kaiser, Brooks; Moore, Sue; Vestergaard, Niels
Abstract: Arctic marine resource governance is analyzed under overarching themes that include: Global Management and Institutions for Arctic Marine Resources, Resource Stewards and Users: Local and Indigenous Co-management, Development and Governance, Multi-scale, Ecosystem-based, Arctic Marine Resource Management. Six papers present the thematic analyses built on respected theory from various disciplines with empirical applications across five Arctic countries (Russia, Canada, U. S., Iceland, Norway) and the Central Arctic Ocean. The timing of this special issue is ideal since one theme of the U. S. chairmanship of the Arctic Council is stewardship of the Arctic Ocean with a focus on marine environmental protection, Arctic ocean acidification, Arctic indigenous people as well as search and rescue. Highlights: Arctic marine resource governance of Arctic and non-Arctic states is fragmented. Indigenous co-management of Arctic marine resources can be successful. The U. S. and Canada differ in strategies to address oil spill risks in the Arctic. Icelandic fisheries quotas have led to other than perfect competition. Managing invasive species as commercial fisheries in Norway has ongoing challenges.